A new species, Agapetus kaengkrungensis (Trichoptera: Glossosomatidae) from Kaeng Krung National Park, southern Thailand with the distribution map of the genus in Thailand - Vadon, Solomon Boga; Pongtipati, Pattira; Laudee, Pongsak (Zootaxa, 2021)
The male of a new species of caddisfly, Agapetus kaengkrungensis n. sp. (Glossosomatidae) is described and illustrated from Kaeng Krung National Park, Surat Thani Province, southern Thailand. Agapetus kaengkrungensis n. sp. is distinguished from other species by the characters of segment IX and inferior appendages. The distributions of the Agapetus spp. of Thailand are mapped and discussed.